Policy and Impact Analysis of Smelter Development in Morowali Sulawesi: A Multidisciplinary Review of Social, Economic and Environmental Aspects - Galih Wahyu PRADANA; Sekar Ayu KUNCARAVITA; Aldea Noor ALINA (East Asian Policy)
This article provides an in-depth analysis of the impact of constructing the Morowali Industrial Park smelter in Indonesia. Empirical findings indicate that the local economy benefits tremendously through the creation of additional jobs and overall regional economic growth. However, the local economy faces serious environmental problems, alongside social issues. To ensure that the benefits outweigh disadvantages, it is crucial to implement stringent environmental regulations and facilitate community participation in decision-making.